Pengaruh Latihan Drill dan Tingkat Konsentrasi Terhadap Hasil Shooting Petanque - Baktiyaningsih, Lulus; Setyawati, Heny; Rahayu, Setya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the effect of drill training and concentration level on the results of petanque shooting. This research uses an experimental method with a 2x2 factorial design with pretest and posttest. The research population was 45 UNNES petanque UKM athletes with samples taken using purposive sampling so that 40 people were obtained. The instruments used are the petanque shooting test and the grid concentration test. Analysis of this research data uses normality tests, homogeneity tests, and hypothesis tests. The results show 1) differences in the influence of training on petanque shooting results, Fcount (6.099) > Ftable (2.87) and α p = 0.018 < 0.05. 2) the difference in the influence of concentration on shooting results, Fcount (26,492) > Ftable (2.87) and α p = 0.000 < 0.05. 3) interaction of drill training and concentration level on petanque shooting results, Fcount (4.627) > Ftable (2.87) and α p = 0.038 < 0.05. Research conclusions: There is a difference in the influence of jack pralon half and jack pralon high drill training on petanque shooting results. There is a difference in the influence between high concentration and low concentration on shooting results. There is an interaction between drill training and concentration level on petanque shooting results, high concentration with jack pralon half training is better for petanque shooting results. Keywords: Drill Training, Concentration Level, Petanque Shooting